2018
DOI: 10.1007/s11356-018-3145-1
|View full text |Cite
|
Sign up to set email alerts
|

Stress response of NAD+-dependent formate dehydrogenase in Gossypium hirsutum L. grown under copper toxicity

Abstract: Cotton (Gossypium hirsutum L.), which is not directly involved in the food chain, appears to be a suitable candidate to remove heavy metals from the food chain and to be a commercial plant which could be planted in contaminated soils. The key point of this approach is selection of the right genotype, which has heavy metal resistance or hyperaccumulation properties. Therefore, in the present study, two G. hirsutum genotypes, Erşan-92 and N-84S, were grown under copper stress and investigated to obtain further i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 38 publications
0
3
0
1
Order By: Relevance
“…Even if most of them presented a down-regulation tendency, such as ubiquinol oxidase 1a, whose function as alternative oxidase is known to be important during both biotic and abiotic stress (Vanlerberghe, 2013), three proteins were up-regulated in response to heat: formate dehydrogenase, thioredoxin H-type and glutathione S-transferase DHAR3. As previously mentioned, formate dehydrogenase is a universal stress protein involved in the responses to various abiotic and biotic stresses by catalysing the oxidation of formate, a byproduct of ROS scavenging, and maintaining a reducing environment in the cell (Kurt-Gür et al, 2018). Several studies have demonstrated that heat can induce the synthesis of this enzyme (Ren et al, 2019) and its abundance seems to be regulated by the 26S proteasome (McNeilly et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Even if most of them presented a down-regulation tendency, such as ubiquinol oxidase 1a, whose function as alternative oxidase is known to be important during both biotic and abiotic stress (Vanlerberghe, 2013), three proteins were up-regulated in response to heat: formate dehydrogenase, thioredoxin H-type and glutathione S-transferase DHAR3. As previously mentioned, formate dehydrogenase is a universal stress protein involved in the responses to various abiotic and biotic stresses by catalysing the oxidation of formate, a byproduct of ROS scavenging, and maintaining a reducing environment in the cell (Kurt-Gür et al, 2018). Several studies have demonstrated that heat can induce the synthesis of this enzyme (Ren et al, 2019) and its abundance seems to be regulated by the 26S proteasome (McNeilly et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Formate dehydrogenases (FDH) are a group of enzymes that catalyze the oxidation of formate to carbon dioxide, which are also involved in energetic metabolism and pathways related to stress response 38 . The FDH activity increased significantly with increasing copper concentrations to help cotton scope with copper toxicity 39 . Under hypoxic stress, FDH activity is significantly increased in the potato tubers 40 .…”
Section: Discussionmentioning
confidence: 99%
“…The colorimetric assay was performed using 200 m m sodium phosphate (pH 7.5) containing 0.4 mg ml −1 nitroblue tetrazolium (NBT) and 0.03 mg ml −1 PMS with or without 2 μg recombinant protein, 1.62 m m NAD + and 162 m m formate (Kurt‐Gür et al., 2018). In this assay, NBT receives electrons from NADH via PMS and generates blue‐purple formazan.…”
Section: Methodsmentioning
confidence: 99%